IN VITRO ACTIVITY OF VANCOMYCIN AND DAPTOMYCIN AGAINST HEALTHCARE-ASSOCIATED METHICILLIN-RESISTANT STAPHYLOCOCCUS AUREUS ISOLATED FROM CLINICAL SPECIMENS - Kumari, Jyoti; Shenoy M, Shalini; M, Chakrapani; K, Vidyalakshmi; Bhat K, Gopalkrishna (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The present cross-sectional study was conducted to determine minimum inhibitory concentration (MIC) of daptomycin and vancomycin to clinical isolates of healthcare-associated-methicillin-resistant Staphylococcus aureus (HA-MRSA). Methods: Centers for Disease Control and Prevention Criteria were used to define HR infections due to MRSA. Antibiotic susceptibility testing was done by Kirby–Bauer disk diffusion method. MIC of vancomycin and daptomycin was determined by Agar dilution method and E-test, respectively. Results of antibiotic susceptibility testing and MIC were interpreted as per Clinical Laboratory Standard Institute guidelines. Results: A total of 110 strains of MRSA were isolated from healthcare-associated infections. All were susceptible to daptomycin, linezolid, and teicoplanin. A total of 106 isolates were vancomycin susceptible and four were vancomycin-intermediate S. aureus (VISA). MIC of vancomycin were 2 µg/ml. All MRSA isolates were susceptible to daptomycin. Four VISA strains had daptomycin MIC 1 µg/ml. Conclusion: The present study showed the emergence of VISA among HA-MRSA isolates with high MIC for vancomycin. Although all HA-MRSA isolates were susceptible to daptomycin, VISA isolates had high daptomycin MIC. This indicates that daptomycin may not be used as an alternative choice for VISA infections. Keywords: Healthcare-associated methicillin-resistant Staphylococcus aureus, Vancomycin, Daptomycin. 90 90 and MIC 50